2002
DOI: 10.1152/japplphysiol.00974.2001
|View full text |Cite
|
Sign up to set email alerts
|

5-HT3receptors mediate inflammation-induced unmasking of functional tachykinin responses in vitro

Abstract: Exogenously applied tachykinins produce no measurable electrophysiological responses in the somata of vagal afferent neurons [nodose ganglion neurons (NGNs)] isolated from naive guinea pigs. By contrast, after in vitro antigen challenge of nodose ganglia from guinea pigs immunized with chick ovalbumin, approximately 60% (53 of 89) of NGNs were depolarized an average of 13 +/- 1.2 mV by substance P (SP; 100 nM; n = 53). Receptor antagonists and enzyme inhibitors were utilized to screen a number of mast cell-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In this regard, following ingestion of a meal, the levels of platelet-free 5-HT rise from approximately 25 to 88 nmol L )1,34 as vagal afferent neurons from several species, including the rat, display both 5-HT 2 and 5-HT 3 receptors, one may reasonable assume that vagal afferent neurons may be additionally excited by the increase in circulating 5-HT levels following ingestion of a meal. [21][22][23][24] In addition, therefore, to inducing the release of 5-HT from enterochromaffin cells and activating 5-HT 3 receptors on vagal afferent terminals within the GI tract, glucose may also increase the ability of vagal sensory neurons and nerve fibers to respond to the released 5-HT, providing a means by which the vagal afferent signal can be amplified and/or prolonged in a temporally distinct manner. Trafficking of 5-HT 3 receptors via regulated exocytosis has been shown previously to occur in expression systems, 35,36 but, to our knowledge, this is the first functional and physiological demonstration of 5-HT 3 receptor trafficking within peripheral neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, following ingestion of a meal, the levels of platelet-free 5-HT rise from approximately 25 to 88 nmol L )1,34 as vagal afferent neurons from several species, including the rat, display both 5-HT 2 and 5-HT 3 receptors, one may reasonable assume that vagal afferent neurons may be additionally excited by the increase in circulating 5-HT levels following ingestion of a meal. [21][22][23][24] In addition, therefore, to inducing the release of 5-HT from enterochromaffin cells and activating 5-HT 3 receptors on vagal afferent terminals within the GI tract, glucose may also increase the ability of vagal sensory neurons and nerve fibers to respond to the released 5-HT, providing a means by which the vagal afferent signal can be amplified and/or prolonged in a temporally distinct manner. Trafficking of 5-HT 3 receptors via regulated exocytosis has been shown previously to occur in expression systems, 35,36 but, to our knowledge, this is the first functional and physiological demonstration of 5-HT 3 receptor trafficking within peripheral neurons.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 This phenomenon does not appear to be restricted to central vagal terminals, however, as vagal afferent neurons are also capable of altering their neurotransmitter phenotype in response to physiological conditions. [18][19][20] As vagal afferent neurons also display functional 5-HT 3 receptors [21][22][23][24] and are capable of responding to circulating blood glucose levels, this study aimed to determine whether extracellular glucose can modulate the response of GI vagal afferent neurons to 5-HT via alterations in 5-HT 3 receptor density and/or function.…”
Section: Introductionmentioning
confidence: 99%
“…Different subtypes of 5HT receptors exist in sensory neurons which mediate inhibitory or stimulatory effects on SP release [21]. It has been shown that endogenous 5HT release and 5HT 3 receptor activation are critical for unmasking SP receptors in nodose neurons in allergic inflammation [22]. So it is possible that the pro-inflammatory effect of centrally 5HT mediated, at least partly, via interaction with 5HT 3 receptors on neurons which release SP.…”
Section: Discussionmentioning
confidence: 99%
“…In guinea‐pigs, allergic inflammation leads to the ‘unmasking’ of neurokinin 2 (NK2) receptors on sensory nerves originating in the nodose ganglia 58 . This effect appears to be mediated by serotonin (via 5‐HT 3 receptors), which may be increased during inflammatory responses 59 . Although the functional consequences of these neurochemical alterations have yet to be fully described, changes in neurotransmitter phenotype and receptor expression may have profound influences on defensive reflex physiology.…”
Section: Afferent Mechanisms Of Altered Cough Reflex Sensitivitymentioning
confidence: 99%